The relationship between gut microbiota and spontaneous bacterial peritonitis in patients with liver cirrhosis - a literature review - Roxana-Emanuela Popoiag; Anca Pantea-Stoian; Adrian P. Suceveanu; Andra I. Suceveanu; Laura Mazilu; Irinel R. Parepa; Laura M. Serban; Mihai Paunica; Catalina Motofei; Carmen Fierbinteanu Braticevici (Journal of Mind and Medical Sciences, 2019)
Gut microbiota is an essential component in the pathogenesis of liver cirrhosis and its complications. There is a direct relationship between the gut and the liver called the gutliver axis through which bacteria can reach the liver through the portal venous blood. However, it remains unclear how bacteria leave the intestine and reach the fluid collection in the abdomen. A series of mechanisms have been postulated to be involved in the pathogenesis of spontaneous bacterial peritonitis (SBP) and other complications of liver cirrhosis, including bacterial translocation, bacterial overgrowth, altered intestinal permeability and dysfunctional immunity. The hepatic function may also be affected by the alteration of intestinal microbiota composition. Current treatment in SBP is antibiotic therapy, but lately, probiotics have been the useful treatment suggested to improve the intestinal barrier and prevent bacterial translocation. However, studies are contradictory regarding their usefulness. In this review, we will summarize the literature data on the pathogenesis of spontaneous bacterial peritonitis concerning the existence of a relationship with the microbiota and the useful use of probiotics.